Preparation and Characteristics of Acid-soluble Soybean Protein Hydrolysates - Liqi FAN; Yang LIU; Bao YANG; Yi YU; Wu LI; Lei LIU; Zhunchun LI; Ao ZHA; Jucai XU (Shipin gongye ke-ji)
In this work, the enzymatic hydrolysates of soybean protein were treated with acid at different pH values, and the differences in physicochemical properties, taste characteristics and in vitro antioxidant activities of the products were analyzed. Meanwhile, changes in peptide composition were also analyzed based on the peptidomics analysis to investigate the preparation characteristics of acid-soluble soy protein hydrolysates. The results showed an evident decrease in nitrogen recovery rate and total free amino acid contents after the acid treatment process. Nevertheless, only slight changes were observed in the antioxidant activity and peptide molecular weight distribution of the products.When the hydrolysates were acid-treated at pH5, the content of bitter hydrophobic amino acids was reduced, thereby the bitterness decreased. Additionally, the peptides identified from the enzymatic hydrolysates of soybean protein were primarily presented with the length values ranging from 2 to 5. For products treated at pH3, more pentapeptides and octapeptides were observed through the peptidomic analysis, while minor changes were observed for those treated at pH5. Moreover, compared with the product treated at pH3, the bitter taste of the hydrolysates could be evidently reduced after the acid treatment at pH5. Therefore, the acid treatment at pH5 was recommended for preparation of the acid-soluble soybean protein hydrolysates, which could help to achieve higher product yield (about 54.50%), better antioxidant activity and more potential antioxidant peptides (368), as well as a consistent peptide distribution and lower bitter taste.